Market orientation of smallholders in selected grains in Ethiopia: implications for enhancing commercial transformation of subsistence agriculture - Gebremedhin, Berhanu; Hoekstra, Dirk (International Livestock Research Institute, 2008)
In spite of the policy decision of the Government of Ethiopia (GoE) to commercialize subsistence agriculture, there is a dearth of information on the commercialization process and marketing behaviour of smallholders in Ethiopia. This paper attempts to contribute to redressing this gap of knowledge for the cereal crops of teff, wheat and rice; the pulse crops of haricot beans and chickpea; and an oil crop (niger seed). Data for the study was collected from districts where these crops are important market-oriented commodities. Analysis of the variation in market participation of households in these crops in areas where the crops are already important market-oriented commodities offers a unique opportunity to gain insight into the determinants of the commercialization behaviour of households. About 65–77% of households produce these market-oriented commodities on about 27–44% of the total cultivated area. About 47–60% of the produce of these market-oriented commodities is sold. The important market places for producers of these commodities are the district town markets and markets located at the peasant associations (PA). Markets in other district towns or regional markets are rarely used by producers. Wholesalers and retailers are the most important buyers from producers. Econometric analyses show that market orientation of households is affected by factors related to household demographic characteristics, human and physical capital endowment, distance to markets, institutional support services, and village level factors of population density, agricultural labour wage and rainfall. Our results imply that market interventions to improve the gains to producers need to target district level markets. Special attention is required to female-headed households in the process of commercial transformation of subsistence agriculture. The comparative advantage of female-headed households may not be in grain production. Population control measures may contribute to commercial transformation of subsistence agriculture through their effect of reducing household subsistence requirements. Improving the operations of factor markets of land, traction and farm labour could contribute to enhancing market orientation of farm households. Alternatively, institutional arrangements to improve household access to land and traction power could contribute to market orientation of households. Market access remains an important factor for market orientation of households, implying the need for interventions to develop market infrastructure. The extension and credit services that were designed to achieve food security objectives need to be re-examined to adopt them to the policy of commercial transformation of subsistence agriculture Ethiopia is following. In particular, the institutionalization and development of marketing extension services warrants emphasis.